A 2D generic multi-surface cohesive zone model for simulating FRP-to-concrete mixed-mode debonding failure. (15th September 2022) - Nie, Yu; Xie, Tian-Yu; Chen, Guang-Ming; Zhao, Xin-Yu; Lv, Jian-Bing
Highlights: A 2D generic multi-surface cohesive zone model is proposed for simulating FRP-to-concrete debonding failure; The model can simulate mix-mode debonding failure in a consistent way; Implicit backward Euler integration method is applied; The model is validated by comparing predictions with various test results. Abstract: This paper proposes a 2D generic multi-surface cohesive zone model to simulate the debonding failure process of FRP-to-concrete joints within the framework of plasticity theory. The model combines a tension cut-off yield surface with a Coulomb friction yield surface, which can accurately predict the coupled mixed-mode debonding behaviour. Non-associated flow rule is adopted by the Coulomb friction yield formulation to reproduce the dilation effect, while the tension cut-off criterion is responsible for simulating the separation in the normal direction between two bonded substrates. Given the potential non-convergence problems caused by the presence of vertex region at the intersections between two yield surfaces, a remedy measure using the implicit backward Euler integration method incorporating Koiter's rule and coupled independent state variables is applied. The proposed 2D interface model is versatile, and its accuracy has been validated by comparing the predicted results with their test counterparts from literature in different aspects, including the capacities of capturing mixed-mode failure, dilation behaviour, lateral compression effect, FRP deformation, and local bond stress-slip relationship. The model's good compatibility with the constitutive relationship of CDP (concrete damaged plasticity) is also demonstrated.